High-throughput microRNA sequencing in the developing branchial arches suggests miR-92b-3p regulation of a cardiovascular gene network - Goldsworthy, Sian; Losa, Marta; Bobola, Nicoletta; Griffiths-Jones, Sam (Frontiers in Genetics, 2025)
Vertebrate branchial arches (BAs) are a developmental paradigm, undergoing coordinated differentiation and morphogenesis to form various adult derivative tissues. MicroRNAs can strengthen gene regulatory networks (GRNs) to promote developmental stability. To investigate microRNA-mediated regulation in BA development, we generated a novel microRNA-sequencing dataset from mouse BAs. We identified 550 expressed microRNAs, of which approximately 20% demonstrate significant differential expression across BA domains. The three most posterior BAs and the connecting outflow tract (PBA/OFT) express genes important for cardiovascular development. We predicted microRNA-target interactions with PBA/OFT-expressed cardiovascular genes and found target sites for miR-92b-3p to be enriched. We used a dual luciferase assay to validate miR-92b-3p interactions with two transcripts encoding the fundamental cardiac transcription factors (TFs), Gata6 and Tbx20. Furthermore, we demonstrated that miR-92b-3p mimic can downregulate endogenous GATA6 and TBX20 in human embryonic stem cells (hESCs) undergoing cardiomyocyte differentiation, confirming microRNA-target binding can occur in a cardiac cell type. miR-92b-3p has previously been shown to target transcripts encoding for two other cardiac TFs, Hand2 and Mef2D. Therefore, we hypothesise that miR-92b-3p acts to stabilise cardiovascular GRNs during PBA/OFT development, through multiple microRNA-mediated regulatory networks.